Legal professional privilege and confidentiality - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Masum, Ahmad (CLJ Malaysia Sdn. Bhd., 2025)
Since the “legal professional privilege” is that of the client and not that of the lawyer, it essentially protects all communications between a client and a lawyer from being disclosed without the permission of the client.8 The rationale behind this legal principle is to safeguard the client from any disclosure of communications made with the lawyer and thereby prejudicing the client in the future.9 However, the privilege can only be claimed if the communication in question is confidential. Therefore, communication is no longer privileged if it ceases to be confidential